Investigating the Effects of Nitrogen and Silicon-dioxide Nanoparticles on Sunflower in the Semi-arid Region - Aghdam, Masoud; Janmohammadi, Mohsen; Sabaghnia, Naser (Annals of Arid Zone, 2025)
A field experiment was conducted to assess the impact of varying levels of nitrogen fertilizer (40, 80, and 120 kg ha-1) and different concentrations of silicon dioxide nanoparticles (50, 100, and 150 ppm) on the growth characteristics of sunflower in Northeast Iran. Results showed nitrogen application improved the plant height, the number of leaves, canopy width and decreased the diameter of the stem. The longest leaves were recorded in the plants grown with application of 80 kg N ha-1 followed by spray of 100 ppm SiO2. The application of 80 and 120 kg ha-1 nitrogen significantly increased the head diameter, and the foliar application of 100 ppm SiO2 under high nitrogen application. Nitrogen utilization improved the positive effect of SiO2 on achene yield components. Maximum head weight was obtained with application of 80 kg N ha-1 followed by spray of 100 ppm SiO2 while maximum achene weight was achieved for plants grown with application of 80 kg N ha-1 followed by spray of 50 ppm SiO2. Application of high doses of silicon dioxide nanoparticles (100 and 150 ppm) decreased the weight of achene while nitrogen application increased this component. Foliar application of concentrated Si solution decreased the number of achene in the head. High achene yield was recorded following application of 80 kg N ha-1 with 100 ppm SiO2 and 120 kg N ha-1 and 50 ppm SiO2. The results indicated that the application of 40, 80, and 120 kg ha-1 of nitrogen increased the achene yield 21%, 57%, and 52% compared to the control, respectively. Taken together, the results exhibited that the use of 80 kg ha-1 of nitrogen along with foliar spray with a 50 or 100 ppm of silicon dioxide nanoparticles can significantly improve the sunflower performance.